CERPEN â€œKISAH PILOT BEJOâ€ KARYA BUDI DARMA (ANALISIS SEMIOTIKA ROLAND BARTHES) - Astika, I Made (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
The purpose of the research is to reveal the meaning of Budi Darmaâ€™s â€œKisah Pilot Bejoâ€ short story, by the deployment of Roland Barthes semiotic approaches. The data unit is in form of text taken from the short story and collected by documentation method. The data is analyzed descriptively by the use of short story structure reading method. â€œKisah Pilot Bejoâ€ shows the depiction of Indonesian aviation transportation failure, begins with the unprofessionalism of the pilot, the incredible aviation company, and the conditions of the planes which actually not feasible to fly. The representation is an outright critic for the government to seriously focus their attention toward the national aviation system professionally, transparently, and responsibly.Keywords: Kisah Pilot Bejo, Roland Barthes semiotic